Drug-Coated Balloon in Primary Percutaneous Coronary Intervention - Hui Zhao; Runran Miao; Fei Lin; Guoan Zhao (Journal of Interventional Cardiology)
According to the latest coronary interventional guidelines, a drug-eluting stent is the recommended reperfusion therapy in primary percutaneous coronary intervention (pPCI). However, deficiencies and defects, such as in-stent restenosis (ISR), incomplete stent apposition, stent thrombosis, reinfarction after stent implantation, long-term dual antiplatelet drug use, and adverse reactions of metal implants, plague clinicians and patients. Drug-coated balloon (DCB), which delivers antiproliferative agents into the vessel wall without stent implantation and leaves no implants behind after the procedure, is a novel option for percutaneous coronary intervention and has proven to be a promising strategy in cases of ISR, small vessel coronary artery disease, and bifurcation lesions. However, most of the available experience has been gained in elective percutaneous coronary intervention, and experience in pPCI is lacking. The current evidence for the use of DCB-only in pPCI was discussed and analyzed in this review.